Measurements of Group Delay and Chromatic Dispersion of Hollow-Core Fiber Using a Frequency Domain Method - Xin Chen; Jason E. Hurley; John L. Nord; Ilia Nikulin; Paulo Dainese; Michael Sauer; Ming-Jun Li (Photonics)
Although hollow-core fibers are intended to be single-mode, they can potentially carry slightly higher-order mode content depending on the specific fiber structure. The presence of one or more higher-order modes makes the measurement of group delay and chromatic dispersion difficult if one relies on an instrument that is designed to work with single-mode fiber, in particular, a commercial instrument. In this work, we present the measurements of hollow-core fibers using a frequency domain method by acquiring the complex transfer function over a range of modulation frequencies. The measurement technique is immune to the higher-order mode nature presented by some of the hollow-core fibers. We measured hollow-core fibers with a five-capillary structure and a six-capillary structure. We obtained the absolute group delay as well as the chromatic dispersion information. In particular, we were able to measure one hollow-core fiber with at least two modes. The measured chromatic dispersion values are consistent with the modeling and those reported in the literature.